Do kinematics of the pelvis and lower limb vary between novice and highly trained cyclists? - Chapman, A. R.; Vicenzino, B.; Blanch, P.; Dowlan, S.; Hodges, P. W. (ISB Congress, 2006)
The purpose of this study was to determine if kinematic variations are likely to account for differences in leg muscle recruitment between novice and highly trained cyclists.